A single-centre, placebo-controlled, double-blind randomised cross-over study of nebulised iloprost in patients with Eisenmenger syndrome: A pilot study. (15th January 2020) - Nashat, Heba; Kempny, Aleksander; Harries, Carl; Dormand, Natalie; Alonso-Gonzalez, Rafael; Price, Laura C.; Gatzoulis, Michael A.; Dimopoulos, Konstantinos; Wort, Stephen J.
Abstract: Background: Pulmonary arterial hypertension (PAH), is a rare and progressive disease with a high morbidity and mortality. Prostanoid pulmonary vasodilators are the most effective treatment for idiopathic and connective tissue associated PAH. Nonetheless, data examining their safety and efficacy in patients with Eisenmenger syndrome the most severe form of PAH, that is, related to cyanotic congenital heart disease (CHD-PAH) remains limited. Aim: To evaluate safety and the clinical efficacy of nebulised iloprost in patients with Eisenmenger syndrome who are on maximum background oral PAH therapy. Methods: This pilot study was a randomised, double-blind, placebo-controlled, cross-over study. Patients were randomised to receive nebulised placebo or iloprost for 12 weeks and were then crossed over, with a 7–14-day washout. The primary endpoint was a change in 6-minute walk distance (6MWD). Results: Sixteen patients (11 females, aged 47.3 ± 9.8 year) were recruited, twelve completed the study. All were in WHO-FC III, with a resting oxygen saturation of 84 [81–87] % and a median 6MWD of 290 [260–300] m. There was no significant difference in the primary endpoint between nebulised iloprost (0[−4–9]m) and placebo (10 [−15–51]m), p  = 0.58. There were no safety concerns with nebulised iloprost. Conclusions: Our pilot study provides preliminary evidence that the addition of nebulised iloprost to maximum oral PAH therapy did not improve the primary endpoint of 6MWD. Nebulised iloprost was well tolerated with no significant safety concerns in CHD-PAH. Highlights: Eisenmenger syndrome (ES) is an important subgroup of pulmonary hypertension complicating congenital heart disease. Advanced therapies have improved the lives of patients with pulmonary arterial hypertension (PAH) Advanced therapy use in ES is derived from non-controlled data in ES and controlled data on other forms of PAH Iloprost, a potent vasodilator, did not improve 6 min walk distance in patients with ES Iloprost was safe to use in patients with ES.